2022
DOI: 10.3803/enm.2022.301
|View full text |Cite
|
Sign up to set email alerts
|

Euthyroid Thyroperoxidase Antibody Positivity during Pregnancy, to Treat or Not to Treat?

Abstract: Thyroperoxidase antibody (TPOAb) positivity is a well-known risk factor for thyroid dysfunction during pregnancy and is associated with a suboptimal response to thyroidal stimulation by human chorionic gonadotropin. About 75% of TPOAb positive women are euthyroid and there seems to be a higher risk of predominantly miscarriage and preterm birth in this subgroup. Nonetheless, clinical decision making with regards to gestational levothyroxine treatment remains difficult due to a lack of large randomized trials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
1
1
Order By: Relevance
“…However, the anti-TPO Abs in this study were positive in only about 58.9% of the samples, which may be due to the small sample size. Likewise, we found that a positive anti-TPO Abs state could not be predicted by age or gender, despite previous studies suggesting that older age and a positive family history were risk factors for anti-TPO Ab positivity [11].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the anti-TPO Abs in this study were positive in only about 58.9% of the samples, which may be due to the small sample size. Likewise, we found that a positive anti-TPO Abs state could not be predicted by age or gender, despite previous studies suggesting that older age and a positive family history were risk factors for anti-TPO Ab positivity [11].…”
Section: Discussioncontrasting
confidence: 99%
“…While anti-TPO Abs in patients with AITD can fix complement, destroy thyroid cells, and competitively inhibit enzymatic activity [ 10 ], the risk factors for anti-TPO Abs presence in GD include a higher age, iodine deficiency or excess, a family or personal history of AITD, along with idiopathic and autoimmune causes. Furthermore, paradoxically, smoking and pregnancy appear to decrease the risk of positive anti-TPO Abs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because thyroid peroxidase and thyroglobulin antibodies belong to the immunoglobulin G class of antibodies, they pass the placental barrier and are often detectable in fetal plasma during pregnancy and during the first several weeks of postnatal life [24]. However, they do not seem to have a meaningful impact on fetal and neonatal thyroid function [25], and our findings are in line with this commonly accepted view.…”
Section: Discussionsupporting
confidence: 87%